Effect of tofacitinib, a Janus kinase inhibitor, on haematological parameters during 12 weeks of psoriasis treatment. (31st October 2013) - Strober, B.; Buonanno, M.; Clark, J.D.; Kawabata, T.; Tan, H.; Wolk, R.; Valdez, H.; Langley, R.G.; Harness, J.; Menter, A.; Papp, K.
Abstract : What's already known about this topic? The Janus kinase (JAK) inhibitor tofacitinib has demonstrated efficacy for the treatment of moderate‐to‐severe chronic plaque psoriasis in a phase IIb trial. JAK‐dependent signalling is integral to haematopoiesis. Thus, the haematological effects of tofacitinib require evaluation. What does this study add? Over 12 weeks, tofacitinib conferred dose‐dependent, tolerable changes in selected haematological parameters. Effects on red blood cells and haemoglobin appeared nonprogressive; effects on reticulocytes may reflect dynamic, compensatory changes in erythropoiesis. Effects on neutrophils and lymphocytes appeared transient; eosinophils returned to near baseline levels 4 weeks after treatment cessation. Likely mechanisms may involve partial inhibition of haematopoietic cytokine signalling via JAKs. Longer‐term evaluation is warranted. Summary: Background: The Janus kinase (JAK) inhibitor, tofacitinib, has shown efficacy for the treatment of psoriasis in a phase IIb trial (A3921047; NCT00678210). Objectives: To report haematology data from the phase IIb trial, given the importance of JAK‐dependent signalling in haematopoiesis. Methods: Patients with moderate‐to‐severe chronic plaque psoriasis were randomized to receive tofacitinib 2, 5 or 15 mg, or placebo, twice daily over 12 weeks. Blood samples were collected at screening, baseline, weeks 2, 4, 8 and 12 during treatment, and weeks 14 and 16 during off‐treatment follow‐up. Results: Baseline haematology was similar across patients receiving tofacitinib 2 mg ( n  = 49), 5 mg ( n  =   49) or 15 mg ( n  =   49), or placebo ( n  =   50). Tofacitinib conferred dose‐dependent decreases in haemoglobin, haematocrit and red blood cell counts, while reticulocyte counts initially declined, before recovering by week 8, and exceeding baseline levels after treatment cessation. With regard to white blood cells, tofacitinib had no clear dose‐dependent effects on basophils or monocytes, but appeared to be associated with transient or reversible dose‐dependent decreases in neutrophil and eosinophil counts and transient increases in lymphocyte counts, which were primarily attributable to increases in B‐cell counts. Natural killer cell counts declined with tofacitinib. Conclusions: Tofacitinib conferred tolerable, dose‐dependent changes in haematological parameters during short‐term administration in patients with psoriasis. The effects did not appear to be progressive, and were often transient or reversible.